The spider genus Cyrioctea Simon on Chañaral Island (Pingüino de Humboldt National Reserve, Atacama, Chile): description of a new species, and the male of Cyrioctea cruz Platnick (Araneae, Zodariidae) - Grismado, Cristian José (2016)
A faunistic survey on Chañaral Island, Atacama, near the northern Pacific coast of Chile, allowed the discovery and description of a new species of the spider genus Cyrioctea: C. islachanaral sp. nov., based on females collected by pitfall traps. Strikingly, this new species shares morphological characters with some Southern African representatives of this genus rather than with the species of continental South America. The male of the species C. cruz Platnick, previously known from continental Chile (northern Coquimbo), is described for the first time based on specimens collected in the same locality.